PERINGATAN TRADISI HAUL KYAI GEDE CEPER SEBAGAI SARANA EDUKASI PEMBENTUKAN MORALITAS MASYARAKAT SEMBUNGJAMBU, PEKALONGAN - Keysya Ainina; Moh. Yasir Alimi (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
The Haul tradition of Kyai Gede Ceper in Sembungjambu Village, Pekalongan, is an annual religious ritual that persists and has a significant influence on the formation of community morality. This study aims to analyze how the series of haul rituals, cultural symbols, and social practices within it function as a means of tradition based moral education. Using a qualitative approach with observation techniques, in-depth interviews, and documentation, this study is analyzed using Clifford Geertz's symbolic perspective to interpret the symbolic meanings that emerge from ritual practices. Research results show that the haul tradition encompasses two main categories of morality: spiritual morality, manifested through the recitation of khotmil Qur'an, tahlil, and mass haul; and social morality, manifested through socializing, cross-generational participation, and community organizational solidarity. These ritual symbols form webs of meaning that affirm religious identity as well as the social ethics of the community. Furthermore, the strategy of collective involvement of all layers of society keeps haul relevant as a transgenerational educational mechanism that transmits moral values in dailylife.